Nationality Diversity of Bank Boards - Nedelchev, Miroslav (Naše gospodarstvo/Our economy, 2018)
The aim of this paper is to carry out a comparative study for nationality diversity in bank boards. The study covers practices of board diversity of nine commercial banks. The data are compared for subsidiary banks in Bulgaria and their parent banks from the home country. The study defines a high degree of nationality diversity in subsidiary banks. The Bulgarian banks have a higher number of foreign members on boards compared to their parent banks. The good practices on board diversity in Bulgarian banks are a consequence of their subordination in European financial conglomerates and are aimed to reduce agent conflicts.